Cognitive Dissonance and Fertility Rates: A Comparative Analysis of Attitudes toward the Gender Division of Labour in East Asian and Western Industrial Societies. Issue 1 (11th January 2021) - Hong, Cheng-Huei; Gilbert, Neil
Abstract : Based on data from the International Social Survey Program (ISSP), this study examines the extent to which cognitive dissonance regarding egalitarian attitudes toward the gender division of labour are associated with fertility rates in sixteen societies, representing Anglo American, Northern European, Western European and East Asian regimes. The findings show that although levels of support for gender equality in the realms of the family and the market are positively associated with fertility rates, an even stronger relationship to fertility emerges when weighing the differences between the levels of support for gender equality in each realm. The findings lend some corroboration to McDonald's hypothesis, which suggests that declining fertility rates are influenced by contradictory expectations between gender equality for women in the home and market.